From philology to English studies : language and culture in the nineteenth century - Momma, H. (Cambridge : Cambridge University Press, 2013)
'The study of English language and literature in Britain changed dramatically between the end of the eighteenth century and the beginning of the twentieth. From Philology to English Studies explores the contribution of philology to this evolution. Haruko Momma charts both the rise and fall of philology from antiquity to the late eighteenth century, and the impact of modern philology on the study of modern languages and literatures. Focusing in detail on the work of key philologists in the nineteenth century, Momma considers how they shaped European discourse and especially vernacular studies in Britain: William Jones' discovery of Sanskrit in British India gave rise to Indo-European studies; Max M$1#7H(Bler's study of this same language helped spread the Aryan myth to the English-speaking world; the OED achieved its greatness as a post-national lexicon through the editorship of the Scottish dialectologist'--s
1. Introduction: where is philology? -- 2. Philological awakening: William Jones and the architecture of learning -- 3. The Anglo-Saxon revolution: John Mitchell Kemble and the paradigm -- 4. The Philological Society of London: lexicography as national philology -- 5. The professor and the reader: vernaculars in the academy -- Epilogue: the closing of the phase of philology.
Includes bibliographical references (pages 193-215) and index.
Keywords: Philology -- History -- 19th century; Comparative linguistics -- History -- 19th century; English language -- History -- 19th century; Language and culture -- History -- 19th century